![x4 - 14x2y2 + y4 x4 - 14x2y2 + y4](https://tex.z-dn.net/?f=x4+-+14x2y2+%2B+y4)
Answers
Answered by
5
Answer:
x⁴-14x²y²+y⁴
x⁴-14x²y²+y⁴ = (x²-y²+2√3xy)(x²-y²-2√3xy)
Step-by-step explanation:
x⁴-14x²y²+y⁴
= x⁴-2x²y²+y⁴ -12x²y²
= [(x²)²-2x²y²+(y²)²] - 12x²y²
= (x²-y²)² - (2√3xy)²
= (x²-y²+2√3xy)(x²-y²-2√3xy)
Therefore,
x⁴-14x²y²+y⁴
= (x²-y²+2√3xy)(x²-y²-2√3xy)
•••♪
Answered by
1
Answer:
May it helps you....
Attachments:
![](https://hi-static.z-dn.net/files/db0/c44ba62f6b50c07083e4b8bc794033a8.jpg)
Similar questions
Hindi,
7 months ago
Math,
7 months ago
Physics,
1 year ago
Math,
1 year ago
Accountancy,
1 year ago
Computer Science,
1 year ago